Public pensions and growth - Stéphane Lambrecht; Philippe Michel; Jean-Pierre Vidal (European Central Bank (ECB), 2001)
This paper investigates the relationship between the size of an unfunded public pension system and economic growth in an overlapping generation economy, in which altruistic parents finance the education of their children and leave bequests. Unlike the existing literature, we model intergenerational altruism by assuming that children's income during adulthood is an argument of parental utility. Unfunded public pensions can promote growth when families face liquidity constraints preventing them from investing optimally in the education of their children. We consider two alternative ways of financing a public pension system, either by levying social contributions in a lump-sum manner or in proportion to labour income. We find that there is no case for unfunded public pensions in economies where bequests are operative. By contrast, there exists a growth-maximising size of the public pension system in economies where bequests are not operative and individuals are sufficiently patient
Keywords: H55; I20; D91; 330; Education; Growth; Public pension